Trans-Pacific Partnership (TPP) agreement: An empirical analysis on the impact of Malaysia’s trade on economic growth - Zainal Abidin, Irwan Shah; Jantan, Mohd Dan; Haseeb, Muhammad (2015)
This study focuses primarily on Malaysia’s economic interests in the TPP agreement.It provides a comparative economic analysis of the countries currently in the TPP and describes the Malaysia trade flows with these countries at the bilateral level and in relation to the countries’ economic linkages with the rest of the world.It also provides information on the existing trade agreements of TPP countries.As such, this study aims to explore the impact of Malaysia’s international trade with TPP countries on the economic growth of Malaysia.To achieve this objective, this study will make three different variables, that is, the Malaysian import from TPP countries, export to TPP countries and total trade with TPP countries.For this purpose, time series panel data from 2000 to 2014 have been utilized. The results of fixed effect model and random effect model suggest that imports from TPP countries negatively impact on economic growth of Malaysia.Whereas, exports and total trade with the rest of the world have contributed positively to the economic growth of Malaysia. Hence, the Malaysian government and policymakers should emphasize more on the pros and cons on Malaysian imports from TPP member countries.Moreover, there is a need to look more into boosting exports to TPP countries to stimulate economic growth of Malaysia.